Development and Validation of Volume Prediction Model for Balangeran (Shorea balangeran (Korth.) Burck) In Central Kalimantan - Qirom, Muhammad Abdul Qirom (Forestry Department, University of Muhammadiyah Makassar, 2018)
Estimation model of tree volume must be high in accuracy and precisions to estimate stand potential precisely. This paper determines and validates the estimation model of Shorea balangeran volume grown in Central Kalimantan, Indonesia. There were three phases of model development which include 52 trees for model progress, 23 trees for model validation, and 10 trees for external model validation. The calculation model used linear and non-linear models with diameter, diameter and height, and diameter and height combination as independent variables. The criteria of the best model was determined by statistical analyses such as coefficient determination, relative and aggregative deviation, bias, precisions and accuracy of estimation, AIC (Akaike’s Information Criterion). The result of the study showed that the model with diameter as single variable was not complied with the selected best model criteria (aggregative deviation; AD< 1 % and relative deviation: RD< 8 %). The addition of tree height on model estimation increased the coefficient determination of 6.54% and the model with diameter and height as independent variable was satisfied with the criteria (AD and RD criteria). The best model of Balangeran was with coefficient determination of 89.77 %. However, the best model was not applicable for other sites with different stand characteristics